1996
DOI: 10.1002/pssa.2211580213
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Damping in AlMgSi Industrial Alloys

Abstract: The micromechanisms of high temperature damping in an AlMgSi industrial alloy are investigated by mechanical spectroscopy. The alloy in the as‐received T6 state shows a relaxation peak at 483 K (1 Hz) with an activation energy H = 1.6 eV and a limit relaxation time τ0 = 1.3 × 10−18 s. It is also found in solubilized, quenched and overaged samples. The internal friction maximum is attributed to a mechanism in which: a) lattice dislocations are firmly pinned by β″ or β′ precipitates and b) lattice dislocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…2) In the past decade, several research works have been devoted to the vibration behavior of Al-Mg-Si alloys. [3][4][5][6] With respect to the effect of aging conditions, it was found that aging conditions significantly affect the resonant vibration properties, such as vibration deformation feature and damping capacity. The peak aged samples possess a poor damping capacity mainly due to the decrease in dislocation mobility.…”
Section: Introductionmentioning
confidence: 99%
“…2) In the past decade, several research works have been devoted to the vibration behavior of Al-Mg-Si alloys. [3][4][5][6] With respect to the effect of aging conditions, it was found that aging conditions significantly affect the resonant vibration properties, such as vibration deformation feature and damping capacity. The peak aged samples possess a poor damping capacity mainly due to the decrease in dislocation mobility.…”
Section: Introductionmentioning
confidence: 99%
“…26, 29, and 30͒ followed by another peak around 900 K. 30 The exact temperature of the peaks depends on the annealing temperature and the frequency. 29,30 Figure 4 shows a large increase in the loss at 500 K. Also, the loss angle of our ribbon ͑thickness b =25 m͒ should be higher than the loss angle of the bulk metal because of surface losses. 20 The sensitivity of the DSMG does not depend on the loss angle directly but instead depends on the relaxation time , see Eq.…”
Section: Violin Mode Lossesmentioning
confidence: 89%
“…This researcher observed an internal-friction peak at about 473 K (about 2.25 Hz), the activation energy of which was 1.3 eV. However, recently CarrenÄ o- Morelli et al (1996) proposed a new interpretation. The drift in the peak temperature during ageing was explained by a change in vacancy content within the precipitates.…”
Section: Origin Of the Relaxation Peakmentioning
confidence: 96%